Contribuições para o uso de células estromais mesenquimais no reparo de feridas cutâneas e no transplante de pele em coelhos - Treichel, Tiago Luís Eilers (2014)
This thesis was carried out in three distinct stages; the first being intended to analyzing the cell therapy of skin wound healing in rabbits. The aim of this work was to evaluate the healing potential of the stromal vascular fraction (SVF) and mesenchymal stromal cells (MSC) and to compare which one presents better efficiency and ease of use. For this study we used 15 rabbits divided into three groups. A skin wound of 4 cm2 was created in all rabbits. The animals of group A did not receive any kind of treatment, whereas in group B they were treated with SVF from adipose tissue, and in group C they were treated with MSC. Histological analysis demonstrated that the healing stages occurred more satisfactorily in the treated groups. In the statistical analysis, the two treated groups showed no significant difference between them, but when compared with the control group there was a significant difference. It was found that both the use of SVF as well as MSC are viable and showed better results that the control, even making the resulting scar of the process aesthetically acceptable. In the second step we determined the degree of oxidative stress in the cultured MSC. The goal of this study was to evaluate the isolation and culture of MSC from adipose tissue samples from three rabbits, processed immediately after harvest and within 12 or 24 hours intervals, keeping them in culture until the ninth pass. The samples from each animal were divided into three new samples, the first of which was processed immediately after harvest, and the others within 12 and 24-hour intervals. The dichlorofluorescein diacetate (DCFH-DA) assay demonstrated that immediate cultures had an increased overall rate of reactive oxygen species (ROS) from the fourth passing, cultured cells after 12 hours, from the third passage and after 24 hours, after the third pass, but with another episode during the ninth passage. The PicoGreen test demonstrated that the immediate cultures obtained a greater release of DNA only in the seventh and ninth passages, 12 hours, cell death only in the ninth passageway and 24 hours, during the last passes evaluated. In conditions in which the experiment was conducted, and based on the results, we conclude that adipose tissue may be cultured until 24 hours after harvest, since kept in ideal conditions. In the third step, the possible immunosuppressive potential of MSC was tested. The aim of this work was to assess the viability of the fresh allograft skin in rabbits, using as an immunomodulatory agent, mesenchymal stromal cells, associated or not to cyclosporine. To prepare this experiment, 20 New Zealand White male rabbits were used, randomly divided into four experimental groups. Group A: only transplantation done. Group B: application of MSCs on days -1, 0, 3, 7 and 10, always associated with cyclosporine. Group C: only the application of MSC in the same periods that in the previous group. Group D: only injectable cyclosporine. The Tukey test, at 5% probability level, was used to compare the means. The graft survival rates were 7.2 days (± 3.49) for group B, 11.5 days (± 3.58) for group C, 9.0 days (± 1.22) for group D, and 13.0 days (± 1.41) for group A. Interleukins were evaluated in groups A, B and C, and at this point, the combined use of cyclosporine with the MSC, appears to have been beneficial for inhibition of some of these factors. It can be concluded that both application of cyclosporine as well as the halogen MSC, when administered alone were not able to increase the rate of skin graft survival, but both therapies, when associated, were responsible for causing a faster rejection of transplanted tissue than the control group. Still, the measured values of the key pro-inflammatory interleukins were lower when this association occurred.